Should Sweden join the EMU? An analysis of general equilibrium effects through trade - Kari E. O. Alho (The Research Institute of the Finnish Economy (ETLA), 2011)
The paper considers whether Sweden should join the EMU as based on general equilibrium (GE) effects through reduced trade barriers linked to the single cur-rency. We use in this evaluation a gravity model for trade in Europe derived and estimated in the paper, and the estimates of trade barriers linked to EMU reached in the literature. First, we present an alternative derivation of the gravity equation for foreign trade, which is explicitly based on monopolistic competition in the export markets. In contrast to the usual specification, our model allows for the realistic assumption of asymmetry in mutual trade flows. We then present a straightforward methodology how to carry out a simulation, based on the estimated model, of GE effects related to a change in a trade barrier. Numeri-cally, we apply this to analyse the effects of a possible Swedish entrance into EMU. The effects are quite clearly in favour of EMU enlargement, and do not indicate a trade diver-sion effect either for the incumbent EMU countries or the rest of the European countries. However, a stochastic simulation of the effects reveals that there is a substantial uncer-tainty related to the effects of such a change in policies.
Keywords: F12; F15; 330; EMU; Sweden; gravity model; general equilibrium effects; trade barriers; Allgemeines Gleichgewicht; Gravitationsmodell; Handelshemmnisse; Eurozone; Schweden